Non-motor Symptoms in Chinese Patients With Isolated Generalized Dystonia: A Case–Control Study - Li, Shanglin; Wang, Lin; Yang, Yingmai; Qiao, Lei; Zhang, Dingding; Wan, Xinhua (Frontiers in Neurology, 2020)
Background: Previous studies have indicated that non-motor symptoms are primary problems in focal dystonia, but limited data are available about non-motor problems and their correlation with motor severity in generalized dystonia (GD). Methods：In the present study, we performed a case-control study and enrolled isolated inherited or idiopathic GD patients and age- and sex-matched healthy controls (HC). Clinical characteristics, motor symptoms, non-motor problems, including psychiatric co-morbidity, sleep problems, fatigue, and quality of life (QoL) were assessed in both groups using various rating scales and assessments. Results: Thirty-three patients with GD and 33 controls were enrolled. Significant higher scores on depression and anxiety (p<0.001) were shown in GD compared with HC, whereas the frequency of obsessive-compulsive disorders approached that of HC (p=0.238). Patients with GD also had significantly higher Pittsburg Sleep Quality Index (PSQI) and fatigue scores than HC, whereas no difference was observed in excessive daytime somnolence. In GD, QoL was more impaired, with statistically lower scores in both physical and mental components. Psychiatric rating scales did not correlate to motor severity or disease duration but might influence quality of sleep. Subgroup analysis suggests non-motor manifestations differ with different etiologies in GD. Conclusion: This study suggests that non-motor symptoms in GD, such as psychiatric problems, are likely to be primary determinants not correlated to motor severity, which may also affect quality of sleep and fatigue.